Associations Between Vitamin K and Suicide Attempts in Patients with Depression: A Case-Control Study [Response to Letter] - Wang ST; He XY; Le J; Sun T; Peng R (Journal of Inflammation Research, 2024)
Shao-Ting Wang,* Xiao-Yun He,* Juan Le, Ting Sun, Rui Peng Department of Clinical Laboratory, Institute of Translational Medicine, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People’s Republic of China*These authors contributed equally to this workCorrespondence: Rui Peng, Department of Clinical Laboratory, Institute of Translational Medicine, Renmin Hospital of Wuhan University, Wuhan, Hubei, 430060, People’s Republic of China, Email pengruiwec@163.com